Penerapan Model Pembelajaran Demonstrasi untuk Meningkatkan Hasil Belajar Membaca Puisi Kelas IV SD Kristen X Kotamobagu - Hetty J. Tumurang (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to obtain the results of an analysis of how the application of the demonstration learning model to improve reading poetry learning outcomes through the application of the demonstration learning model for the fourth grade students of SD Kristen X Kotamobagu. The method used in this research is quantitative analytical method with 4 stages, namely planning, action, observation and reflection. The location of this research is SD Kristen X Kotamobagu. Interviews were conducted with fourth grade students of SD Kristen X Kotamobagu. The results of the study indicate that the learning process of fourth grade students at SD Kristen X Kotamobagu by using a demonstration learning model can improve student learning outcomes. In accordance with the results of observations and tests, the learning steps using the applied demonstration learning model continue to progress. Learning outcomes continue to increase, it can be seen from the results of the evaluation of the first cycle reaching 68.15 and the second cycle reaching 94.47. So that in the second cycle the learning process has been successful and has reached the KKM that has been determined by the school, which is 75%. A significant increase occurred in the second cycle, where the average value of the class had exceeded the KKM, which was 94.47%. And the results of this study can be concluded that by applying the demonstration learning model can improve student learning outcomes in learning to read poetry. From the conclusion, further research development should be carried out by involving a more diverse reflection process as needed.